The effect of low-cycle fatigue parameters on damage accumulation near a hole. (December 2019) - Matvienko, Yury; Pisarev, Vladimir; Eleonsky, Svyatoslav
Abstract: A new destructive method for the quantitative determination of damage accumulation in the stress concentration zone has been proposed and verified. Damage accumulation in the vicinity of the hole was created by means of preliminary low-cycle fatigue loading of specimens with holes. After that, consecutive narrow notches, emanating from the hole, are performed under the constant external load for each specimen to estimate the effect of damage accumulation on fracture mechanics parameters. A measurement of deformation response, caused by local material removing in the form of a notch, is carried out by electronic speckle-pattern interferometry (ESPI). In this case, the initial experimental data has a form of interference fringe patterns, which are essential for deriving of in-plane displacement components in the vicinity of the notch. The transition from in-plane displacement components to values of the stress intensity factor (SIF) and the T-stress follows from the relationships of modified version of the crack compliance method. The curves of the crack mouth opening displacement, the stress intensity factor and the T-stress versus of notch length and number of cycles for notches emanating from open holes at different stages of low-cycle fatigue are constructed to analyse the effect of the stress range and the stress ratio on fatigue damage accumulation. The damage accumulation function is expressed in an explicit form on a base of distributions of the normalized stress intensity factor as a function of the number of cycles. Highlights: Destructive method for the quantitative determination of fatigue damage accumulation is proposed and verified. The fracture mechanics parameters are estimated by optical interferometric measurements of deformation response. The effect of low-cycle fatigue parameters on damage accumulation is analyzed. The fatigue damage accumulation function is presented in an explicit form.